Penerapan Pembuktian Terbalik Berimbang Dan Terbatas Pada Harta Hasil Peredaran Narkotika - Lingga, Nimrod Gandatua; Jauhari, Iman; Harianto, Dedi (ARBITER: Jurnal Ilmiah Magister Hukum, 2021)
The purpose of this research is to know the regulation on balanced and limited reversal of the burden of proof in the legal provisions in Indonesia and implementation of balanced and limited reversal of the burden of proofin the Ruling No. 427/Pid.B/2014/PN.Mdn and the obstacles and efforts in implementing balanced and limited reversal of the burden of proof .The research used juridical normative and descriptive analytic method by analyzing all legal provisions related to the balanced and limited reversal of the burden of proof. The data were gathered by conducting library research and field research method.Based on the research problems, it can be concluded that, the regulation on reversal of the burden of proof has been stipulated in the Indonesian legal provisionsthe process of evidence in the Ruling No. 427/Pid.B/2014/Pn.Mdn does not follow the balanced and limited reversal of the burden of proofthe obstacles in the implementationfrom its, legal substance, legal structure and legal culture.